Peritoneal Dissemination of Hepatoid Carcinoma of the Ovary Treated with Cytoreductive Surgery and Hyperthermic Intraoperative Intraperitoneal Chemotherapy. (10th June 2013) - Cascales Campos, Pedro Antonio; Gil Martinez, Jose; Torroba, Amparo; Machado, Francisco; Parrila Paricio, Pascual
Abstract : Hepatoid carcinoma of the ovary (HCO) was first reported in 1987 in 5 cases of malignant ovarian tumors which were similar to hepatocarcinoma in the histological analysis. We report the first case in the literature of a patient diagnosed with HCO treated using HIPEC after extensive cytoreductive surgery, and we discuss the value of this therapeutical option in patients with HCO.